Charlesworth and Cain company law - Cain, T. E.; Charlesworth, J.; Marshall, Enid A.; Brindley, L. P. K. (London : Stevens, 1977)
In this edition, the author included a fair amount of new material on proposals for the reform of Company Law, including those in the Conservative Government White Paper on Company Reform, the Labour Party Green Paper on the Reform of Company Law and various Companies Bills, in particular the Companies Bill 1973. Another improvement is the treatment of a number of topics: Memorandum of Association (European Communities Act 1972, section 9, and a specimen memorandum of association.
First published in 1932 under title: Principles of company law.
Includes bibliographical references and index.
ne 03/10/2019
Loans
Keywords: Corporation law